Efficacy and safety of catheter ablation combined with left atrial appendage occlusion for nonvalvular atrial fibrillation: A systematic review and meta‐analysis. Issue 1 (2nd December 2019) - Jiang, Ying; Li, Fanghui; Li, Dongze; Cheng, Yisong; Jia, Yu; Fu, Hua; Pu, Xiaobo; Hu, Hongde; Jiang, Jian; Zeng, Rui
Abstract: Atrial fibrillation (AF) is currently the most prevalent arrhythmia in clinical practice, with stroke being one of its major complications. Combining catheter ablation and percutaneous left atrial appendage occlusion (LAAO) into a "one‐stop" intervention could reduce stroke incidence in selected high‐risk patients and, at the same time, relieve AF symptoms in a single procedure. This meta‐analysis analyzed the efficacy and safety of catheter ablation combined with LAAO for nonvalvular AF. PubMed, EMBASE, and the Cochrane Library were searched from inception to April 2019 to identify relevant citations. Efficacy indexes were procedural success, AF recurrence, stroke/transient ischemic attacks (TIA), and device‐related thrombus (DRT). Safety indexes were all‐cause death, major hemorrhagic complications, and pericardial effusion/cardiac tamponade. The incidence rate of events (ratio of events to patients) and 95% confidence interval (CI) were calculated as summary results. A forest plot was constructed to present pooled rates. Eighteen studies (two randomized controlled trials and 16 observational studies) were included. The results showed that one‐stop intervention has significant efficacy and safety, with procedural success of .98 (95% CI, .97‐1.00), AF recurrence of .24 (95% CI, .15‐.35), stroke/TIA of .01 (95% CI, .00‐.01), DRT of .00 (95% CI, .00‐.01), all‐cause mortality of .00 (95% CI, .00‐.00), cardiac/neurological mortality of .00 (95% CI, .00‐.00), major hemorrhagic complications of .01 (95% CI, .00‐.02), and pericardial effusion/cardiac tamponade of .01 (95% CI, .00‐.01). A single procedure with catheter ablation and LAAO in AF is a feasible strategy with significant efficacy and safety.